Impact of time between thrombolysis and endovascular thrombectomy on outcomes in patients with acute ischaemic stroke - Wagner, Lora; Mohrbach, Desiree; Ebinger, Martin; Endres, Matthias; Nolte, Christian H.; Harmel, Peter; Audebert, Heinrich J.; Rohmann, Jessica L.; Siegerink, Bob (Frontiers in Neurology, 2022)
Background: Benefits of endovascular thrombectomy (ET) after intravenous thrombolysis (IVT) for patients with acute ischaemic stroke (AIS) have been demonstrated, but analyses of the IVT-ET time delay on functional outcomes among patients receiving both treatments are lacking. Methods: We used data from the “Berlin – Specific Acute Treatment in Ischaemic and haemorrhAgic stroke with Long-term outcome” (B–SPATIAL) registry. Between January 1st, 2016 and December 31st, 2019, we included patients who received both IVT and ET. The primary outcome was the 3-month ordinal modified Rankin scale (mRS) score. The IVT-ET time delay was analysed in categories and continuously. We used adjusted ordinal logistic regression to estimate common odds ratios (cOR) and 95% confidence intervals (CI). Secondary analyses involved flexible modelling of IVT-ET delay and dichotomous outcomes. Results: Of 11,049 patients, 714 who received IVT followed by ET were included. Compared with having an IVT-ET window greater than 120 minutes (reference), for an IVT-ET window less than 30 34 minutes, we obtained adjusted cORs for mRS of 0.41 (95% CI: 0.22 to 0.78); and 0.52 (95% CI: 0.33 to 0.82) for 30 to 120 minutes. Secondary analyses also found protective effects of shorter time delays against ‘poor’ functional outcomes at 3 months. Conclusions: In patients with AIS, shorter IVT-ET intervals were associated with better 3-month functional outcomes. While the time-to-IVT and time-to-ET include the time until medical attention is received, the IVT-ET time delays fall entirely within the domain of medical management and thus might be easier to optimize.